CHARACTERISTICS OF BASIC COMPONENTS OF THE SOCIAL AND LABOR RELATIONS REGULATION MECHANISM IN THE UNITED TERRITORIAL COMMUNITIES (International Journal of Innovative Technologies in Economy, 2020)
The study is devoted to the substantiation of the basic components of the mechanism of regulation of social and labor relations in the united territorial communities of Ukraine. The article analyzes the research on the role of the state and local governments in regulating and developing social and labor relations at the local level. The leading world concepts in regulating social and labor relations have been characterized. The purpose and role of local self- government bodies in regulating social and labor relations have been defined. The basic scientific approaches to the concept of “community development” have been investigated. Based on the research, the basic components of the mechanisms of regulation of social and labor relations in the united territorial communities have been identified and their characteristics have been given.